Exploring omnichannel and network design in omni environment. Issue 1 (1st January 2017) - Yadav, Vinay Surendra; Tripathi, Sarsij; Singh, A.R.
Abstract: Modern day supply chain has gone through many changes in order to satisfy the ever increasing needs of customers. One of such change is origin of omnichannel in supply chain which believes in not only satisfying customer's needs but also delighting them. Implementation of omnichannel in practice comes with lots of challenges. These challenges are summarized as major research areas in omnichannel and being explored in this paper through literature. Further, distribution system in omnichannel demands flexibility in distribution which results in restructuring and reconfiguring the practices of traditional supply chain. For this purpose, a mathematical model has been developed under omni environment which provides the facility of flexible distribution for customers. This proposed model is bi-objective in nature which considers sustainability along with minimization of total supply chain cost. To check the feasibility of the proposed model, numerical illustrations have been carried out for two different scenarios. In first scenario, the proposed model is solved for single product and single time period while in second scenario similar conditions are considered for conventional Supply Chain Network (SCN) and is being compared with proposed model. The proposed MILP model is coded in GAMS and solved using CPLEX solver. The results obtained indicate that proposed model possess superiority over conventional SCN in many aspects. The findings from the proposed model ensure that customers are free to avail product and services from their desired channel as per their choice.